(untitled) (Research, Society and Development, 2022)
Bee pollen is a food supplement for its medicinal properties. It has a high concentration of vitamins, mineral salts, proteins, phenolic compounds and carbohydrates, which are beneficial to health. The objective of this work was to evaluate the effects of bee pollen supplementation on the ovarian performance of rats. Fifty pubescent rats were separated into groups maintained with a common feeding routine. Two experimental groups of 15 animals each were supplemented by intragastric administration with 50 mg of bee pollen from Cocos nucifera, for 30 and 90 days. The estrous cycle was followed in the last 12 days of treatment. In the first estrus after treatment, euthanasia was performed by intraperitoneal administration of sodium thiopental (50 mg/kg), to remove the ovaries for making histological sections. The number and types of ovarian structures present were analyzed: secondary follicle, Graafian follicle, atresic follicle and corpus luteum. In animals supplemented for 30 days there was a significant increase in the number of atresic follicles compared to controls. This increase also occurred in the supplemented 90 days compared to 30 days. It was also found a decrease in the number of corpora lutea, suggesting that the effects are time dependent.